Impact of the visceral leishmaniasis elimination initiative on Leishmania donovani transmission in Nepal: a 10-year repeat survey. Issue 2 (February 2020) - Cloots, Kristien; Uranw, Surendra; Ostyn, Bart; Bhattarai, Narayan Raj; Le Rutte, Epke; Khanal, Basudha; Picado, Albert; Chappuis, François; Hasker, Epco; Karki, Prahlad; Rijal, Suman; Boelaert, Marleen
Summary: Background: Nepal launched a visceral leishmaniasis (also known as kala-azar) elimination initiative in 2005. We primarily aimed to assess whether transmission of Leishmania donovani had decreased since the launch of the initiative. We also assessed the validity of the direct agglutination test (DAT) as a marker of infection, in view of future surveillance systems. Methods: We did a repeat survey in a population aged 2 years and older for whom baseline serological data were available from 2006. Data were from three districts in the eastern region of Nepal. The primary outcome of interest was prevalent infection with L donovani as measured with DAT (cutoff value ≥1:3200). We compared age group-specific and cluster-specific seroprevalences in 2016 with those in 2006, using χ 2 tests, with a specific focus on the comparison of seroprevalences in children born between 1996 and 2005, and those born between 2006 and 2015. To estimate the overall adjusted risk ratio for being seropositive in 2016 compared with 2006, we fitted a Poisson model controlling for age, sex, and cluster. Findings: Between Oct 17, 2016, and Dec 26, 2016, we assessed 6609 individuals. DAT prevalence in children younger than 10 years was 4·1% (95% CI 3·2–5·4) in 2006 versus 0·5% (0·1–1·7) in 2016 (p<0·0001). Seroprevalence was lower in 2016 than in 2006 in all age groups and in all repeated clusters. The overall adjusted risk ratio of being seropositive was 0·44 (95% CI 0·37–0·52) for 2016 compared with 2006, and 0·04 (0·01–0·16) in children younger than 10 years. Interpretation: Our findings show that transmission of L donovani in Nepal has decreased significantly between 2006 and 2016, coinciding with the elimination programme. DAT seems useful for monitoring of L donovani transmission. Funding: The Directorate-General for Development Cooperation of Belgium.